RENOVATION DESIGN OF HOUSING SUPPLY SYSTEMS XYZ REALITY - Maradona Herman; Haryanto Haryanto, SKom, MM (Jurnal Sistem Informasi, 2001)
It describes the scientific writing about analyzing the price bidding system renovationat. Reality XYZ, which is still partly use the manual system, and also the constraintsthat are running, for that is analyzing these systems in order to replace manualsystems with computerized systems. With the computerized system the company willfind its ease of processing and benefits as in overcoming delays in the presentation ofa report using database applications such as dBASE V. With the replacement of thenew system aims to improve the flow of data and information works in HousingRenovation Bid System and to determine ways of better operations, for acceptablefast, precise, and accurate.